Disentangling the effects of hedge fund activism on firm financial and social performance - DesJardine, Mark R.; Durand, Rodolphe (Strategic Management Journal, 2020)
Research Summary We investigate how hedge fund activism affects firms' financial and social performance. So far, research has examined either the impact of hedge fund activism on firms' short‐term financial performance, or how other types of shareholder activism affect firms' social performance. Crossing these boundaries with data on 1,324 activist hedge fund campaigns between 2000 and 2016, we find a clear trade‐off associated with hedge fund activism: benefits are shareholder‐centric and short‐lived, reflected in immediate increases in market value and profitability; however, these increases come at a mid‐ to long‐term cost to other stakeholders, captured by decreases in operating cash flow, investment spending, and social performance. We discuss our findings from a multi‐stakeholder perspective to move beyond a polarizing debate about the merits of hedge fund activism. Managerial Summary With hedge fund activism on the rise, determining the consequences of equity ownership by activist hedge funds on target companies' short‐term and long‐term financial and social performance takes on central importance. In this study, we find hedge fund campaigns are associated with three broad sets of outcomes for targeted companies: (a) an immediate but short‐lived increase in market value and profitability, and an immediate and long‐lived decline in operating cash flow; (b) decreases in number of employees, operating expenses, R&D spending, and capital expenditures; and (c) the suppression of corporate social performance. By capturing the range of positive and negative effects on target companies, our study presents the competing implications of hedge fund activism on business and society.